PENGARUH KEPATUHAN WAJIB PAJAK, PENGETAHUAN SISTEM e-FILLING, TAX AUDIT, DAN TAX AVOIDANCE TERHADAP PENERIMAAN PAJAK (STUDI KASUS PADA KPP MAKASSAR UTARA) - Wendy Kala Tikupadang; Carolus Askikarno Palalangan (Paulus Journal of Accounting (PJA), 2020)
The purpose of this research is to find of tax compliance,e-filling, tax audit and tax avoidance and its impact on tax revenue. This research is a quantitativ study. This research use method of data collection that is fieldresearch. The type of data used is primary obtained from quesitionnaires distributed in KPP Pratama in north Makassar. This research was using sample as many as eighty six respondents and the method of determining the sample used convenience sampling method, while the data analysis methodthat used is the multiple regression analysis, with the help of SPSS software version 23. This research result indicates that tax compliance , knowledge a system of e-filling, tax audit and tax avoidance in also had an impact in a significant way on Tax revenue.